2011
DOI: 10.5582/ddt.2011.v5.3.136
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of vincristine-induced neurotoxicity: Possible reversal by erythropoietin

Abstract: Vincristine (VCR) is a potent anticancer drug, but neurotoxicity is one of its most important dose-limiting toxicities. In this study, we investigated the neurotoxic effect of VCR, the possible mechanisms and the role of erythropoietin (EPO) in the protection against VCR-induced neurotoxicity in a rat model. The neurotoxicity of VCR and protective effect of EPO were examined using the tail flick test and by recording electrophysiological characteristics in isolated sciatic nerve. To elucidate the underlying me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…This is in agreement with former reports showing that Epo protects haematopoietic cells from etoposide-induced hemotoxicity in vivo [5] and in vitro [1]. Similarly, Kassem and colleagues reported that administration of vincristine to healthy rats caused a state of glutamate excitotoxicity both centrally and peripherally, and that concomitant application of Epo reversed vincristine-induced neurotoxicity [14]. Unlike MSN, cytotoxicity of etoposide and vincristine on HEK 293 cells was not modified by Epo.…”
Section: Discussionsupporting
confidence: 83%
“…This is in agreement with former reports showing that Epo protects haematopoietic cells from etoposide-induced hemotoxicity in vivo [5] and in vitro [1]. Similarly, Kassem and colleagues reported that administration of vincristine to healthy rats caused a state of glutamate excitotoxicity both centrally and peripherally, and that concomitant application of Epo reversed vincristine-induced neurotoxicity [14]. Unlike MSN, cytotoxicity of etoposide and vincristine on HEK 293 cells was not modified by Epo.…”
Section: Discussionsupporting
confidence: 83%
“…The cooperation of CGRP and nitric oxide has been also confirmed during the present study, where the relatively high degree of the co-localization of CGRP with nNOS (a marker of nitrergic neurons) has been observed in all types of enteric plexuses, especially after the mycotoxins administration. Moreover, it is relatively well established that CGRP expression may change during the neurotoxicity in various parts of the nervous system and/or neuropathies of different origins [48,49,50,51,52], which can confirm neuroprotective and adaptive functions of this neuronal factor.…”
Section: Discussionmentioning
confidence: 99%
“…Vincristine enhances NMDA receptor expression and diminishes CGRP expression, leading to a state of glutamate excitotoxicity that results in axonal degeneration. This may cause increased sciatic nerve excitability [49]. In the thalamus and periaqueductal areas of the brain, oxaliplatin increases protein kinase C activity and upregulates the gamma isoform associated with neuropathic pain development and the epsilon isoform associated with apoptosis [50,51].…”
Section: Central Nervous Systemmentioning
confidence: 99%